Rehabilitation of the Dysmorphic Lower Eyelid From Hyaluronic Acid Filler: What to Do After a Good Periocular Treatment Goes Bad. (16th March 2019) - Skippen, Brent; Baldelli, Ilaria; Hartstein, Morris; Casabona, Gabriela; Montes, Jose Raul; Bernardini, Francesco
Abstract: Background: Chronic, long-lasting edema accompanied by the Tyndall effect as a delayed reaction to hyaluronic acid (HA) filler injection seems to occur exclusively in the eyelids. Objectives: The authors sought to present a treatment algorithm for management of patients with chronic lower eyelid edema as a delayed complication of HA filler injection. Methods: Retrospective study including 61 patients with delayed-onset chronic periocular edema following uneventful HA filler injection in the lower eyelids or cheeks. All patients underwent hyaluronidase enzyme dissolution followed by secondary treatment. Three retreatment options were presented: (1) observation, (2) secondary treatment with HA filler, and (3) lower eyelid blepharoplasty. Results: All patients underwent filler dissolution using hyaluronidase. The mean age was 48 years and 97% of the patients were female. Single treatment was effective in 92% of patients with 8% requiring another hyaluronidase injection to completely eradicate residual edema. Six patients (10%) were satisfied after hyaluronidase only and 6 patients (10%) underwent lower eyelid blepharoplasty. Secondary treatment with HA filler was performed in 48 patients (80%). All were satisfied with final results without further edema in the follow-up period. Conclusions: Delayed-onset chronic lower eyelid edema is a frequent HA-related complication and cause of concern when considering periocular HA treatment. Previous treatment has been limited to either hyaluronidase only or blepharoplasty as a secondary solution after hyaluronidase, with only a minority of patients satisfied. Hyaluronidase, shortly followed by HA filler retreatment, is a safe and effective solution. Level of Evidence: 4: